THE INSTITUTIONS AND ITS BUDGETS OF INFORMATION IN THE SOCIAL ORDER. AN ECONOMIC FOCUS. - Diego Rengifo Lozano (Via Inveniendi Et Iudicandi, 2016)
This article examines, by means of converging economic and legal discourses, the assumptions of necessary information for the social order formulation, which includes clarity about what kind of individuals most be refering as “informed”, and also what kind of information seems to be required in order to founded his rationality patterns regarding the institutional structure.